The intravesical injection of highly purified botulinum toxin for the treatment of neurogenic detrusor overactivity - Asafu-Adjei, Denise; Small , Alexander; McWilliams, Glen; Galea, Giuseppe; Pak , Jamie S.; Chung, Doreen E. (Canadian Urological Association Journal, 2020)
Introduction: We aimed to assess safety and efficacy of incobotulinumtoxinA for the treatment of neurogenic detrusor overactivity (NDO). Methods: We identified patients with NDO confirmed on urodynamics (UDS) and reported urgency incontinence (UI) in those who received intravesical incobotulinumtoxin A injection for neurogenic bladder between November 2013 and May 2017. Parameters studied were daytime frequency, daily incontinence episodes, daily pad use, clean intermittent catheterization (CIC) volumes, symptom scores (UDI6, IIQ7, PGII), and complications. Results: We examined 17 male patients who met inclusion criteria and underwent incobotulinumtoxinA injection. Mean age was 61.2±15.4 years. Fourteen patients (82%) were taking oral antimuscarinics prior to the incobotulinumtoxin A injection. There were improvements in the following parameters: average daily pads (4.5 to 3.3, p=0.465), daily urinary frequency (9.4 to 4.6, p=0.048), daily incontinent episodes (2.5 to 0.4, p=0.033), CIC volumes (400 to 550 mL, p=0.356), hours in between CIC (3.6 to 5.2, p=0.127), and the validated questionnaires UDI6 (30.6 to 7.4, p=0.543) and IIQ7 (52.4 to 6.8, p=0.029). There were no documented symptomatic urinary tract infections (UTIs) within 30 days of injection or reports of de novo urinary retention. Nine of 17 patients (53%) reported being dry at their first postoperative visit. Conclusions: In this preliminary pilot study of a small cohort of males with NDO and UI, significant improvements were seen following incobotulinumtoxinA injection in daily frequency, incontinence episodes, hours in between CIC, and quality of life. Larger-scale and long-term studies are required to confirm these results, but initial findings are promising for wider use of this formulation.